New aspects of application of the alginate-containing biogel from brown algae in probiotic technology - Eugeny V. Yakush; Elena L. Koneva; Natalia M. Aminina; Olga V. Zhuravleva; Gleb D. Mamyrkin (Известия ТИНРО, 2017)
Ability of the bifidobacteria metabolites to break down the sodium alginate molecules is shown for the case of alginate-containing biogel from brown algae with 0.2 % of sodium alginate and the metabolites of bifidobacteria cultured on the semisolid Blaurock media in presence of this biogel. The allocated metabolites caused enzymatic degradation of alginic acids: the lower the alginic acids concentration, the higher the rate of degradation. Effectiveness of the bifidobacteria metabolites to split the sodium alginate depended on stage of the microorganisms development. The samples incubated with metabolites in the stationary phase of growth had viscosity of the polysaccharide solution reduced in 23.0 %, and those incubated in the phase of cell death - in 43.8 %, with the molecular mass of polysaccharide decreased in 1.8-2.0 times. Mechanisms of the sodium alginate utilization by bifidobacteria are discussed.